2015
DOI: 10.1161/circep.114.003057
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Burden and Short-Term Risk of Stroke

Abstract: Background— The temporal relationship of atrial fibrillation (AF) and stroke risk is controversial. We evaluated this relationship via a case-crossover analysis of ischemic strokes in a large cohort of patients with cardiac implantable electronic devices. Methods and Results— We identified 9850 patients with cardiac implantable electronic devices remotely monitored in the Veterans Administration Health Care System between 2002 and 2012. There were 187 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 182 publications
(72 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…Studies performed in patients with cardiac implanted electronic devices have shown that their stroke risk is significantly increased in the presence of device-detected atrial arrhythmias, despite the lack of a close temporal relationship between the detected arrhythmia and occurrence of stroke. [32][33][34] Although we are unable to discern whether the ICM detected incident or prevalent AF, these patients have CHADS 2 and CHA 2 DS 2-VAS C scores of at least 2 and, therefore, are indicated for OAC therapy upon AF detection, regardless of its relationship to the index event. 35 Preventive therapies are usually directed at identifiable causes of future stroke.…”
Section: 19-2131mentioning
confidence: 87%
“…Studies performed in patients with cardiac implanted electronic devices have shown that their stroke risk is significantly increased in the presence of device-detected atrial arrhythmias, despite the lack of a close temporal relationship between the detected arrhythmia and occurrence of stroke. [32][33][34] Although we are unable to discern whether the ICM detected incident or prevalent AF, these patients have CHADS 2 and CHA 2 DS 2-VAS C scores of at least 2 and, therefore, are indicated for OAC therapy upon AF detection, regardless of its relationship to the index event. 35 Preventive therapies are usually directed at identifiable causes of future stroke.…”
Section: 19-2131mentioning
confidence: 87%
“…Because pacemakers in our cohort were not implanted primarily to screen for AF, some cases of brief AF captured on pacemaker interrogations may have been considered clinically insignificant and thus not documented. This is especially true given ongoing uncertainty about the pathogenic significance of brief AF episodes 28, 29. If failure to document AF occurred with similar frequency among black and white patients, nondifferential misclassification of diagnoses would have served to introduce a conservative bias by attenuating associations between race and outcomes and thereby reducing our ability to detect differences in AF rates between white and black patients.…”
Section: Discussionmentioning
confidence: 99%
“…The current study by Dr Turakhia et al 12 addresses this issue by evaluating continuous cardiac rhythm monitoring over 120 days before an ischemic stroke in 187 patients. The unique study design and robust analysis deserve additional examination.…”
Section: Article See P 1040mentioning
confidence: 99%